Effects of Physiological and Biochemical Changes in Females Regarding Obesity - Gul E Raana, Anas Khalil, Zahid Mahmood, Farrukh Sarrfraz, Ayesha Zubair, Noor-Ul-Ain (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Obesity is presently so common inside the world’s population that it is starting to replace under nutrition and infectious diseases as the foremost noteworthy supporter to sick health. In specific, weight is related with diabetes mellitus, coronary heart illness, certain shapes of cancer, and sleep-breathing disorders. Accumulation of excessive fat in body is referred as obesity but this does not take under consideration the morbidity and mortality related with more unassuming degrees of overweight, nor the inconvenient impact of intra-abdominal fat. The worldwide plague of obesity comes about from a combination of genetic susceptibility, expanded accessibility of high-energy nourishments and decreased requirement for physical activity in present day society. Obesity should no longer be assuming as simple issue affecting certain people, but an epidemic that undermines worldwide well being. Objective: To identify the effects of obesity in females and guide regarding healthy life style Material and Methods Study design: Quantitative cross sectional Settings: Sharif Medical City Hospital Duration: Six months i.e. 1st January 2022 to 30th June 2022 Data Collection procedure: It was quantitative cross sectional study. There were 150 females who participated in the study. Informed consent was taken. Age was in between 30-45 years. All participants divided into two groups. In group one normal included 50 females as control group and in group two 100 obese females were present. 5ml venous blood was collected in the vials and stored. Levels of systolic and diastolic blood pressure, serum cholesterol, Triglycerides, LDL, HDL, Blood sugar fasting and BMI were calculated in both groups. Results: The results were significant as p value less than 0.005. All parameters were compared in both normal and obese group and noticed that obese group having high values as compared to normal group in terms of blood pressure both systolic and diastolic, Cholesterol, LDL, HDL, Triglycerides, BSF and BMI levels. Conclusion: Obesity and depressive disorders are common co morbidities and have discrete, however overlapping, pathoetiology. It shows up that weight has direct toxic brain impacts. The co-occurrence of obesity and depressive disorders are exceedingly related with adverse wellbeing outcomes. Treatment openings ought to start with anticipation and pre-emption. Outcomes in weight and depressive disorders may be expanded by an approach that takes these two conditions into consideration. Worldwide, the number of obese individuals is rising at an alarming rate. Present study portrayed the negative effects of obesity in ladies. The findings of this research were a sign for obese ladies with respect to life threatening medical complications since of their overweight. Keywords: Obesity, BMI, LDL, HDL, Cholesterol, Blood Pressure